Different strategies of metabolic regulation in cyanobacteria: from transcriptional to biochemical control - Jablonsky, Jiri; Papacek, Stepan; Hagemann, Martin (Scientific reports, 2016)
Cyanobacteria Synechococcus sp. PCC 7942 and Synechocystis sp. PCC 6803 show similar changes in the metabolic response to changed CO2 conditions but exhibit significant differences at the transcriptomic level. This study employs a systems biology approach to investigate the difference in metabolic regulation of Synechococcus sp. PCC 7942 and Synechocystis sp. PCC 6803. Presented multi-level kinetic model for Synechocystis sp. PCC 6803 is a new approach integrating and analysing metabolomic, transcriptomic and fluxomics data obtained under high and ambient CO2 levels. Modelling analysis revealed that higher number of different isozymes in Synechocystis 6803 improves homeostatic stability of several metabolites, especially 3PGA by 275%, against changes in gene expression, compared to Synechococcus sp. PCC 7942. Furthermore, both cyanobacteria have the same amount of phosphoglycerate mutases but Synechocystis 6803 exhibits only ~20% differences in their mRNA levels after shifts from high to ambient CO2 level, in comparison to ~500% differences in the case of Synechococcus sp. PCC 7942. These and other data imply that the biochemical control dominates over transcriptional regulation in Synechocystis 6803 to acclimate central carbon metabolism in the environment of variable inorganic carbon availability without extra cost carried by large changes in the proteome.
Keywords: regulace genové exprese u bakterií; Gene Expression Regulation, Bacterial; oxid uhličitý; Metabolomics; Systems Biology; Synechocystis; systémová biologie; Gene Expression Regulation, Enzymologic; metabolomika; Carbon Dioxide; Gene Expression Profiling; Synechococcus; Metabolism; metabolismus; stanovení celkové genové exprese; regulace genové exprese enzymů